Situation Report: Bulgaria, 23 April 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Bulgaria Celebrates 100th Anniversary of Lenin's Birth Ideological Vacillations among University Students Revealed Trend toward Increasing Secrecy Persists Bulgarian-Yugoslav Relations Lachezar Avramov to Visit Britain Aldo Moro to Visit Bulgaria